Intermittent fasting inhibits the development of colorectal cancer in APCMin/+ mice through gut microbiota and its related metabolites - Chen, Jia; Su, Rishun; He, Yulong; Chen, Jiong (Frontiers in Microbiology, 2025)
Background and objectivesIntermittent fasting is an emerging dietary approach, but its specific role in colorectal cancer (CRC) is not yet clear. In this study, we investigated the relationship between intermittent fasting and colorectal development in mice.MethodsFirst, APCMin/+ mouse models (a spontaneous model of colorectal cancer) were subjected to intermittent fasting intervention (2 days/week) with regular monitoring of body weight changes. Subsequently, 16S rRNA sequencing and untargeted metabolomics were employed to analyze alterations in fecal microbial community structure and metabolic profiles following the fasting intervention. Tumor development was quantitatively assessed by enumerating CRC lesions using HE staining, while histopathological evaluation was performed to determine the degree of neoplastic progression. Concurrently, western blotting was conducted to examine the expression levels of intestinal barrier function-related proteins. Finally, in vitro validation experiments, including colony formation assay and transwell invasion assay, were performed to investigate the effects of the key microbial metabolite isovaleric acid on the proliferative and invasive capacities of CRC cells.ResultsIntermittent fasting significantly reduced tumor incidence by approximately 50% compared to the control group (1.25 ± 0.38 vs 2.50 ± 0.38 tumors/mouse, P = 0.017) and markedly attenuated tumor progression. 16S rRNA sequencing analysis revealed significant enrichment of two key bacterial genera, Alistipes (P = 0.030) and Odoribacter (P = 0.030), along with a significant reduction in fecal isovaleric acid levels (P < 0.05) in the intermittent fasting group. Furthermore, intermittent fasting effectively controlled body weight gain (P < 0.05) and significantly improved intestinal barrier function (P < 0.05). In vitro experiments further demonstrated that isovaleric acid directly promoted CRC cell proliferation (P < 0.05) and enhanced their invasive capacity (P < 0.05).ConclusionIntermittent fasting suppresses CRC development in mice through its effects on gut microbiota and related metabolites.